ASSESSMENT OF ADHERENCE TO PREVENTIVE MEASURES AGAINST COVID-19 IN MKUSHI DISTRICT (International Journal of Scientific Research and Management (IJSRM), 2022)
The paper suggests that, cost-effective measures, which are not psychologically scary are likely to be more frequently adopted by the public than those that punctuate a dystopia especially social distancing, which was regarded to be at variance with socialization norms. The study was informed by hermeneutic survey and concludes that, handwashing hygiene was the most popular preventative measure with swab testing being the least sort after.